Regulation of 2,4-D Isooctyl Ester on Triticum aestivum and Aegilops tauschii Tillering and Endogenous Phytohormonal Responses - Yu, Haiyan; Cui, Hailan; Chen, Jingchao; Chen, Pingping; Ji, Meijing; Huang, Songtao; Li, Xiangju (Frontiers in Plant Science, 2021)
Tillering is an important agronomic trait essential for the yield of Triticum aestivum and the propagation of Aegilops tauschii. However, the effect of phytohormones on T. aestivum and Ae. tauschii tillering and the underlying regulatory mechanisms remain poorly understood. In the study, we found that T. aestivum and Ae. tauschii exhibited different tillering sensitivities to the auxin herbicide 2,4-D isooctyl ester. At 3 days post-application, tiller bud growth was inhibited by 79.13% in T. aestivum, corresponding to 2.10-fold greater inhibition than that in Ae. tauschii (37.71%). Transcriptome analysis showed that differentially expressed genes (DEGs) in the T. aestivum response to 2,4-D isooctyl ester were mainly enriched in plant hormone metabolism and signal transduction pathways, but similar changes were not observed in Ae. tauschii. A total of nine candidate genes involved in varied tillering responses were selected from the DEGs and validated by quantitative real-time PCR. Endogenous hormone levels were assayed to further verify the RNA-seq results. After 2,4-D isooctyl ester treatment, a significant increase in abscisic acid (ABA) levels was observed in T. aestivum, whereas ABA levels were relatively stable in Ae. tauschii. The herbicide induced more cytokinin (CTK) accumulation in Ae. tauschii than in T. aestivum. External ABA clearly restricted tiller bud growth in both T. aestivum and Ae. tauschii, while 6-benzyl aminopurine had no significant effect. These results indicate that ABA and CTK participate in 2,4-D isooctyl ester-regulated tillering differences between the two species, which will help to further understand the mechanism of the auxin-mediated regulation of tillering.